Book Review: Suffer the Little Children: Genocide, Indigenous Nations and the Canadian State - de Zayas, Alfred (The International Indigenous Policy Journal)

(untitled) (Scholarship@Western (Western University), 2020)
In this timely and morally necessary book, Tamara Starblanket gives particular attention to the forced transfer of Indigenous children to institutions whose raison d’être was to indoctrinate and “educate” them away from their culture and heritage so as to erase Indigenous memory and reprogram younger generations as “Canadians.” These institutions were notorious for death and disease, torture, forced starvation, forced labour, and sexual predation. The book’s structure is well-ordered, the argumentation compelling, but not in phoney “scholarly detachment,” instead in conscious compilation and analysis of the evidence, supported by the force of ethics and a commitment to truth and justice, regardless of zeitgeist and political correctness.